Bi-allelic variants in human WDR63 cause male infertility via abnormal inner dynein arms assembly - Shuai Lu (Nature Publishing Group, 2021)
Abstract Inner dynein arm (IDA), composed of a series of protein complex, is necessary to cilia and flagella bend formation and beating. Previous studies indicated that defects of IDA protein complex result in multiple morphological abnormalities of the sperm flagellum (MMAF) and male infertility. However, the genetic causes and molecular mechanisms in the IDAs need further exploration. Here we identified two loss-of-function variants of WDR63 in both MMAF and non-obstructive azoospermia (NOA) affected cohorts. WDR63 encodes an IDA-associated protein that is dominantly expressed in testis. We next generated Wdr63-knockout (Wdr63-KO) mice through the CRISPR-Cas9 technology. Remarkably, Wdr63-KO induced decreased sperm number, abnormal flagellar morphology and male infertility. In addition, transmission electron microscopy assay showed severely disorganized “9 + 2” axoneme and absent inner dynein arms in the spermatozoa from Wdr63-KO male mice. Mechanistically, we found that WDR63 interacted with WDR78 mainly via WD40-repeat domain and is necessary for IDA assembly. Furthermore, WDR63-associated male infertility in human and mice could be overcome by intracytoplasmic sperm injection (ICSI) treatment. In conclusion, the present study demonstrates that bi-allelic variants of WDR63 cause male infertility via abnormal inner dynein arms assembly and flagella formation and can be used as a genetic diagnostic indicator for infertility males.